Reframing Teacher In-Service Training in Kenya: Recommendations from the Literature. Issue 3 (4th May 2019) - Lowe, Geoffrey M.; Prout, Peter F.
Abstract: Following the rapid expansion of Kenya's education system from 2003, raising education standards has emerged as the country's next major nation-building challenge. There is acknowledgement within Kenya that high education standards are dependent upon the quality of its teachers, which is in turn dependent upon the quality of their pre-service training, and subsequent in-service training. However, amidst accusations that educational standards are declining, in-service training programmes in particular have been singled out as being overly bureaucratic, under resourced, poorly delivered and ineffective in helping to raise teaching standards. Further, the literature suggests that current in-service training programmes are failing to address more fundamental issues surrounding Kenyan teaching professionalism as a whole. This article examines the literature surrounding teacher in-service training in Kenya, as identified by Kenyan researchers, with the aim of synthesising and clarifying the major issues surrounding quality and delivery, and then presents policy recommendations for reframing and building effective in-service provision for the future.